2018
DOI: 10.1186/s40623-017-0766-4
|View full text |Cite
|
Sign up to set email alerts
|

Difference of horizontal-to-vertical spectral ratios of observed earthquakes and microtremors and its application to S-wave velocity inversion based on the diffuse field concept

Abstract: We have been discussing the validity of using the horizontal-to-vertical spectral ratios (HVRs) as a substitute for S-wave amplifications after Nakamura first proposed the idea in 1989. So far a formula for HVRs had not been derived that fully utilized their physical characteristics until a recent proposal based on the diffuse field concept. There is another source of confusion that comes from the mixed use of HVRs from earthquake and microtremors, although their wave fields are hardly the same. In this study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(27 citation statements)
references
References 31 publications
1
21
0
2
Order By: Relevance
“…Numerous studies have demonstrated that both the EHVRs and the MHVRs can be used for site classification; however, for the same station, EHVRs and MHVRs can differ. Kawase et al (2018) determined that MHVRs and EHVRs share similarities, especially from low frequency until their first peak frequency but exhibit significant differences in the higher-frequency range. They argued that this is because microtremors mainly consist of surface waves, so that peaks associated with higher modes would not be prominent, whereas seismic motions mainly consist of upwardly propagating body waves, so that higher mode resonances can be observed in high-frequency domain (Kawase et al, 2018).…”
Section: Ambient Motion Datamentioning
confidence: 99%
“…Numerous studies have demonstrated that both the EHVRs and the MHVRs can be used for site classification; however, for the same station, EHVRs and MHVRs can differ. Kawase et al (2018) determined that MHVRs and EHVRs share similarities, especially from low frequency until their first peak frequency but exhibit significant differences in the higher-frequency range. They argued that this is because microtremors mainly consist of surface waves, so that peaks associated with higher modes would not be prominent, whereas seismic motions mainly consist of upwardly propagating body waves, so that higher mode resonances can be observed in high-frequency domain (Kawase et al, 2018).…”
Section: Ambient Motion Datamentioning
confidence: 99%
“…In order to evaluate seismic hazard, site effects have to be incorporated back correcting the GMPE using HVSR with the appropriate corrections as proposed by Kawase et al (2018). Note that HVSR is a proxy of empirical transfer functions in low frequencies with obvious underestimations in higher frequencies.…”
Section: Cva Cavamentioning
confidence: 99%
“…The source effect is approximately removed. In a recent paper, Kawase et al (2018) suggested to consider the amplification due to vertical motion to avoid overreduction of FAS. However, this requires recordings both in soil and rock sites.…”
Section: Data Processing and Analysismentioning
confidence: 99%
“…In this theory, MHVR can be numerically computed as the imaginary parts of Green's functions, and the theoretical H/V ratio depends on underground layer thickness and elastic properties of soil. Hence the theory allowed for inverting V S profiles from MHVR [13][14][15][16]. One of the authors also examined the applicability of the DFA for the MHVR-based V S profiling and presented the validity of the technique for the site characterizations [17].…”
Section: Introductionmentioning
confidence: 99%